Empowering students in information literacy practices using a collaborative digital library for school projects - Zainab, Awang Ngah; Abrizah, Abdullah (2008)
This paper examines the affordances that a collaborative digital library (CDL) can bring to bear on supporting information literacy practices in the digital information environment. It suggests that the digital library can contribute to student empowerment in information literacy practices while searching, using and collaboratively building the digital library resources. To illustrate this, the authors have been experimenting with the implementation of an integrated information literacy model based on Eisenberg and Berkowitzâ Big 6 Model and describes the CDL features in association with the information literacy dimensions in this model. The CDL focuses on the project-based learning approach to conduct studentsâ project, which supports specific information behaviors that underpin research and learning such as information seeking, browsing, encountering, foraging, sharing, gathering, filtering, and using. Findings regarding teachersâ reception of the digital library are encouraging as they feel the relevance of the digital library to the current requirement of the studentsâ project and its potential to entrench information and resource study skills through project-based learning.